Approach to adolescent health in primary care: Scientific letter - (:unkn) unknown (ORTADOGU AD PRES & PUBL CO, 2007)
It is well established that adolescents who are in a biopsychosocial transition and growth period become vulnerable for some risks as they search new experiences and reinforce their self- perception. In spite of this, frequency of their admittance to health facilities is less than the other age groups. Data show that health risks in this age group are predominantly social in origin than medical, and health interventions at an earlier stage reduce adolescent mortality and morbidity. Instead of waiting for adolescents to visit healthcare facilities with any problem, they should be approached by community oriented service systems answering their needs as they declare. Any point in adolescents' daily life where guidance, counseling, social work or health service is provided may be appropriate to meet with them. For this reason, it is necessary that physicians who work at such positions know and understand the characteristics of this period. The following review addresses the busy primary care physicians to inform them on the common health problems and screening interventions of adolescence and and to allow identification of at-risk adolescents.
Keywords: adolescent health services; primary health care; puberty; PREVALENCE; PREGNANCIES; PREVENTION; GUIDELINES; DISEASE; ANEMIA